Impact on Survival of Timing and Duration of Adjuvant Chemotherapy in Radically Resected Gastric Cancer. Issue 4 (July 2016) - Di Bartolomeo, Maria; Pietrantonio, Filippo; Rulli, Eliana; Poli, Davide; Berenato, Rosa; Caporale, Marta; Bajetta, Emilio; Floriani, Irene; Bajetta, E.; Di Bartolomeo, M.; Catena, L.; Schiavo, M.; et al.
Purpose: Adjuvant chemotherapy improves survival of patients with gastric cancer. Intergroup Trial of Adjuvant Chemotherapy in Adenocarcinoma of the Stomach (ITACA-S) was a phase III study comparing sequential FOLFIRI followed by docetaxel/cisplatin versus 5-fluorouracil monotherapy. The intensive regimen was not superior in terms of disease-free survival (DFS) and overall survival (OS). Methods: The treatment was to be started within 8 weeks from surgery. This analysis evaluates the impact of time from surgery to chemotherapy start (TSC) on outcomes. Results: Out of 1, 106 randomized, 1, 072 patients without major violations of eligibility criteria and receiving at least one treatment cycle were analyzed. Median TSC was 50 days. Chemotherapy was interrupted in 201 (18.8%) cases, whereas it was completed without or with modifications in 277 (25.8%) and 594 (55.4%), respectively. At a median follow-up of 56.9 months, 513 progressions and 472 deaths occurred. A longer TSC was significantly associated with longer DFS (hazard ratio [HR] 0.95; 95% confidence interval [CI] 0.89-1.00; p = 0.05) and OS (HR 0.91; 95% CI 0.86-0.97; p = 0.004), after adjustment for treatment arm, age, sex, primary tumor site, number of resected nodes, and tumor stage. Better treatment compliance was associated with improved survival. Conclusions: Our findings suggest that longer TSC had at least no detrimental effect on DFS and OS, whereas treatment completion had a protective effect. Our findings need to be confirmed prospectively.